Corrective Feedback Applied By The Teacher In Teaching Writing Descriptive Text To The First Year Of SMP Negeri 2 Blora In 2014/2015 Academic Year - Septhyan N, Andhy; , Aryati Prasetyarini, S.Pd, M.Pd; , Nur Hidayat, M.Pd (2015)
This is study is aimed at describing: 1) the types of corrective feedback in teaching writing descriptive text, and 2) the students response to the corrective feedback given by teacher in the teaching writing descriptive text. In achieving the objectives, the researcher used descriptive qualitative as an approach to collect and analyze the data. The research was held in SMP Negeri 2 Blora. The research took 33 students of the first grade students as the subject of the study. The writer gets the data of the research from event, informant, and document. The techniques of collecting data are the observation and interview about the writing teaching learning process. The result of the analysis shows that teacher corrective feedback technique is appropriate and effective for the first grade students of SMP Negeri 2 Blora in teaching writing descriptive text. The teacher in the SMP Negeri 2 Blora combined both oral corrective feedback and written corrective feedback. By using this technique, the students are capable of knowing their errors, the reason and correct it. Especially in oral corrective feedback, the researcher found a new technique that was used by the teacher. So it can facilitate the teaching learning writing process. The students feel comfortable and enjoy the class. The students were not afraid when they made an error. Corrective feedback could come from the other students. This condition make the students active because they could share their idea to another students when there is an error.